Conceptual Metaphors and Proverbs as Interactive Communicative Strategies in a XVII-century Ballad - Borgogni, Daniele (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The article analyzes the presence of Conceptual Metaphors (CMs) in a XVII-century ballad in their interaction with popular proverbs as supplementary symbolizing patterns. The article will try to show the complexity of the mental processing involved in a special case of love disputation, in which CMs are made to interact with proverbs in order to produce implicatures. The use of CMs in the text and their interplay with proverbs and popular wisdom produce some unpredictable perlocutionary effects, which are not only significant indicators of the speakersâŸ ideology and point of view, but also trigger communicative effects and a âœproliferation of meaningsâ which confirm, or disrupt, certain socially âžinheritedâŸ conceptual structures both reflecting and shaping the thought patterns of a community.